Functions of Training in Philosophy for Children (Analytic Teaching, 1990)
Introduction:  When teachers, students or professors attend a Philosophy for Children training conference, they are expected, amongst other things to "lead" some sessions, (more than nonne and less than all).  The activity of leading sessions is modelled by the workshop director or by coaches, and participants are usually advised as to how to prepare for their session "on".  Sometimes participants become confused as to what exactly they are required to do.  And sometimes this confusion is general.  It seems to me that part of the confusion results from the fact that the sessions at the conferences serve at least four different functions.  And sometimes the requirements of the different functions actually conflict with each other.